Structure−Property Relationships in Porous 3D Nanostructures as a Function of Preparation Conditions: Isocyanate Cross-Linked Silica Aerogels - Meador, Mary Ann B; Capadona, Lynn A; McCorkle, Linda; Papadopoulos, Demetrios S; Leventis, Nicholas (Chemistry of materials, 2007)
Sol−gel-derived silica aerogels are attractive candidates for many unique thermal, optical, catalytic, and chemical applications because of their low density and high mesoporosity. However, their inherent fragility has restricted use of aerogel monoliths to applications in which they are not subject to any load. We have previously reported cross-linking of the mesoporous silica structure of aerogels with di-isocyanates, styrenes, or epoxies reacting with amine-decorated silica surfaces. These approaches have been shown to significantly increase the strength of aerogels with only a small effect on density or porosity. Though density is a prime predictor of properties such as strength and thermal conductivity for aerogels, it is becoming clear from previous studies that varying the silica backbone and size of the polymer cross-link independently can give rise to combinations of properties that cannot be predicted from density alone. Herein, we examine the effects of four processing parameters for producing this type of polymer cross-linked aerogel on properties of the resulting monoliths. We focus on the results of 13C CP-MAS NMR, which gives insight to the size and structure of polymer cross-link present in the monoliths and relates the size of the cross-links to microstructure, mechanical properties, and other characteristics of the materials obtained.